The Study of the Impact of Empowering Leadership on Adaptive Performance of Faculties Based on Chain Mediating - Xu, Ying; Zhang, Mengliu (Frontiers in Psychology, 2022)
High-quality faculties are the fundamental guarantee to achieve the connotation development of higher education, so the performance of university faculties determines the quality of teaching and the level of talent cultivation. Facing the change of teaching demand and environment, faculties need to change their working methods spontaneously to achieve high level performance. Relevant empirical studies have shown that empowering leadership has a positive effect on adaptive performance, but some researchers have found that the effectiveness of empowering leadership even has a negative effect. There may be two reasons for the inconsistency in the effectiveness of empowering leadership :(1) there is a lack of in-depth research on the effectiveness of empowering leadership and employees’ performance in existing studies, and the exploration of its theoretical mechanism should be enriched. (2) the effectiveness of empowering leadership may be subject to the conditions of the individual’s characteristics of the empowering. Therefore, the mechanism of empowering leadership on faculties' adaptive performance still needs to be further explored.This study explores the impact of empowering leadership on adaptive performance. Based on Social Exchange Theory and Psychology Empowerment theory, this study explores the mediating role of leadership-member exchange relationship and psychology empowerment in the relationship between them. At the same time, according to Regulatory Focus Theory, the moderating role of promotion focus and prevent focus was studied.We adopted questionnaire survey data including 292 individuals in Changchun, Shijiazhuang and other cities,STATA 15 were conducted to test the hypotheses. The results showed that: （1）Empowering leadership was significantly and positively related to adaptive performance.（2）Leader-member exchange relationship and psychology empowerment play a chain mediating role between empowering leadership and adaptive performance, that is, empowering leadership promotes psychology empowerment by enhancing leadership-member exchange relationship, thereby enhancing theiradaptive performance.（3）Promotion focus positively regulates the relationship between psychology empowerment and adaptive performance. Individuals with promotion focus have a significant positive impact on adaptive performance. Individuals with prevent focus do not weaken the positive impact of psychology empowerment on adaptive performance.